2021
DOI: 10.1007/s13555-021-00602-z
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Efficacy of Biologic Therapies in Moderate-to-Severe Plaque Psoriasis: A Systematic Literature Review and an Enhanced Multinomial Network Meta-Analysis

Abstract: Introduction: Many targeted, systemic therapies have been developed for treatment of moderate-to-severe psoriasis (PsO). A network meta-analysis (NMA) allows for comparison between treatments not directly compared in randomized controlled trials (RCT). This study's objective was to compare the short-term (10-16 weeks) clinical efficacy according to the Psoriasis Area and Severity Index (PASI) among approved biologic treatments for moderate-tosevere PsO using a novel (enhanced) NMA model. Methods: A systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 101 publications
(40 reference statements)
3
10
0
Order By: Relevance
“…In this study, we highlighted that the available biologic therapies for psoriasis are efficacious for paediatric psoriasis. Our study showed that there was a trend to better response to certain biological classes and in particular that anti-IL-17 agents seem to be superior to anti-TNF-alpha therapies in the treatment of paediatric psoriasis, consistent with their corresponding efficacy in adults ( Fahrbach et al, 2021 ; Sbidian et al, 2021 ). However, all the drugs were compared in a blinded, randomised comparison in the short term.…”
Section: Discussionsupporting
confidence: 75%
“…In this study, we highlighted that the available biologic therapies for psoriasis are efficacious for paediatric psoriasis. Our study showed that there was a trend to better response to certain biological classes and in particular that anti-IL-17 agents seem to be superior to anti-TNF-alpha therapies in the treatment of paediatric psoriasis, consistent with their corresponding efficacy in adults ( Fahrbach et al, 2021 ; Sbidian et al, 2021 ). However, all the drugs were compared in a blinded, randomised comparison in the short term.…”
Section: Discussionsupporting
confidence: 75%
“…This study employed the REZ model—an enhancement to the standard multinomial analysis model—to study the comparative efficacy of non-biologic and biologic interventions in achieving improvement in PASI outcomes [ 35 ]. The REZ model addresses the inherent drawbacks of both the binomial and standard multinomial models.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced REZ multinomial model simultaneously addresses the drawbacks of both the binomial and standard multinomial models by adding a random effects component that allows for variability in relative effects across PASI levels, while still ‘borrowing strength’ through modelling a mean effect between each threshold. Fahrbach et al [ 35 ] demonstrated that the REZ model was associated with considerably better model fit for both the FE versus RE in another NMA conducted in patients with moderate to severe PSO. A multinomial model was employed because of the advantage given by such a model of synthesizing data across dependent outcomes (e.g., PASI 50/75/90/100) simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following, psoriasis is increasingly being recognized as systemic inflammatory disorder. The recent development of systemic therapy options and biologics neutralize or inhibit these cytokines and have revolutionized the treatment of moderate to severe psoriasis [for systematic reviews and meta-analyses: ( 27 – 30 )].…”
Section: Introductionmentioning
confidence: 99%